Electro-reduction of N2 on nanostructured materials and the design strategies of advanced catalysts based on descriptors. (January 2022) - Zhao, Chenxu; Xi, Menghui; Huo, Jinrong; He, Chaozheng; Fu, Ling
Abstract: Ammonia is a key industry raw material for fertilizers, chemicals, and energy. The Haber-Bosch process should be performed at high temperatures and pressures and may bring about air pollution. The electro-reduction of N2 (NRR) can be served as the alternative for the Haber-Bosch process due to the mild operation conditions. However, the low faradaic efficiency and NH3 yield rate still hinder the development of NRR. Thus, it is urgently needed to discover catalysts with high performance. Herein, we have provided an up-to-date review of NRR catalysts in both experimental and theoretical works. We have also classified the candidates into metals, metal compounds, and metal-free catalysts. Then, we highlighted the latest achievement of descriptor because it is valid guidance for quick screen of optimal catalysts. The descriptors are proposed mainly based on the N2 activation process of NRR, which can be regulated via many strategies. We thus concluded the effective methods conducted in pioneering works finally. Graphical abstract: Image 1 Highlights: Our review has introduced the pioneering works on N2 electroreduction comprehensively in different aspects. We have classified the pioneering works into metals, metal compounds, and metal-free catalysts. We have also emphasized the descriptor researches in order to highlight the regulation strategies for promising catalysts.